Barriers and facilitators to Water, Sanitation and Hygiene (WaSH) practices in Southern Africa: A scoping review. - Nkeka P Tseole; Tafadzwa Mindu; Chester Kalinda; Moses J Chimbari (PLoS ONE)
A healthy and a dignified life experience requires adequate water, sanitation, and hygiene (WaSH) coverage. However, inadequate WaSH resources remain a significant public health challenge in many communities in Southern Africa. A systematic search of peer-reviewed journal articles from 2010 -May 2022 was undertaken on Medline, PubMed, EbscoHost and Google Scholar from 2010 to May 2022 was searched using combinations of predefined search terms with Boolean operators. Eighteen peer-reviewed articles from Southern Africa satisfied the inclusion criteria for this review. The general themes that emerged for both barriers and facilitators included geographical inequalities, climate change, investment in WaSH resources, low levels of knowledge on water borne-diseases and ineffective local community engagement. Key facilitators to improved WaSH practices included improved WaSH infrastructure, effective local community engagement, increased latrine ownership by individual households and the development of social capital. Water and sanitation are critical to ensuring a healthy lifestyle. However, many people and communities in Southern Africa still lack access to safe water and improved sanitation facilities. Rural areas are the most affected by barriers to improved WaSH facilities due to lack of WaSH infrastructure compared to urban settings. Our review has shown that, the current WaSH conditions in Southern Africa do not equate to the improved WaSH standards described in SDG 6 on ensuring access to water and sanitation for all. Key barriers to improved WaSH practices identified include rurality, climate change, low investments in WaSH infrastructure, inadequate knowledge on water-borne illnesses and lack of community engagement.